ANNIE SULLIVAN'S PORTRAYAL OF EDUCATIONAL SUCCESS IN THE MIRACLE WORKER MOVIE BY ARTHUR PENN - Muhammad Fauzan Cahyoko; Sutaryo Sutaryo; Yetty Yetty (Jurnal Bilingual, 2024)
The purpose of this study is to find out Annie Sullivan's character based on the psychological perspective in The Miracle Worker movie by Arthur Penn and to find out the factors that contributed to Annie Sullivan's success in educating that showed in The Miracle Worker movie. The methodology used in this research is qualitative descriptive. The primary data was The Miracle Worker movie, whereas secondary sources of data were libraries, websites, essays, articles, journals, and all printed things. Data analysis techniques in this study consisted of listening, reading, classifying, interpreting, and concluding. The results of the research showed there are seven Annie Sullivan personalities based on the psychological perspective and eight factors that contributed to Annie Sullivan's success in educating.